An updated list of butterfly (Lepidoptera, Rhopalocera) fauna of Tadoba National Park, Chandrapur, Maharashtra, Central India - Ashish D. Tiple; Shatanik S. Bhagwat (Journal of Insect Biodiversity and Systematics, 2023)
The present study was carried out to reveal the checklist of butterfly species in the Tadoba National Park, Chandrapur area of 623 sq. km. Study was carried out from 2011 to 2021. A total of 134 species were recorded, with an addition of 27 new records for Tadoba National Park. Of the total, 60 species were very common, 34 species were common, 9 were frequent common, 19 were rare, and 12 were very rare. Most of the butterflies recorded belong to the Nymphalidae (43 species) with 4 new records. Of Lycaenidae, 41 species with 12 new records. In Pieridae 19 species with 3 new records were recorded. A total of 20 Hesperiidae species with 6 new records and 10 species were recorded from the Papilionidae with 2 new records and one species recorded from the family Riodinidae. About 12 species of the recorded ones come under the protection category of the Indian Wild Life protection Act 1972. The study provided an updated list of butterflies of Tadoba National Park.